REINTERPRETASI HADIS NABI TENTANG STEREOTIPE TERHADAP PEREMPUAN (Perspektif Muhammad Al-Ghazali) - Erni Asih (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
Gender issues is the discourse and movement to achieve equality role, This gender movement rovelves around problems that occur against women, are like stereotyping, marginalization, subordination and the double burden of violence. This article discusses how reinterpretation hadith about female stereotypes according to Muhammad Al-Ghazali that will be discussed more detail the text of hadith impressed bias gender to be understood comprehensively by the readers and eliminate the negative lebel against women.